A review on the most valuable biomarkers in epilepsy (Fasa University of Medical Sciences, 2018)
Background & Objective: Epilepsy is a common neurological disorder with the prevalence of 50 million in the world. Despite of many researches and introducing of different anti-epileptic drugs, 30% of patients suffer from refractory seizures. Biomarkers are the measurable indicators to detect the physiological and pathological condition. Biomarkers in epilepsy can be utilized for prediction, diagnosis, severity and effectiveness of drugs. Conclusion: The efficacy of biomarkers in the prognosis and evaluation of drugs effectiveness is notable. Owing to the diversity of clinical symptoms of epilepsy, various biomarkers have been presented. Among wide-ranging biomarkers, some structural biomarkers such as imaging and electrophysiology including electroencephalogram are the most usable biomarkers. These evidences suggest more investigations to introduce biomarkers that are more practical.